Menakar Kepailitan Digital: Urgensi Reposisi Perlindungan Konsumen dalam Bangkrutnya Platform E-Commerce di Indonesia: Perlindungan Konsumen dalam Bangkrutnya Platform E-Commerce - Abdalla, RM. Sheridan; Rindiani, Anis; Pawari, Rahmiati Ranti (Universitas Muhammadiyah Ponorogo, 2025)
The rapid growth of Indonesia's digital economy has introduced various e-commerce platforms that serve as the backbone of national electronic commerce. However, the phenomenon of bankruptcy or collapse of major e-commerce platforms, as seen in several national marketplace cases, raises serious concerns regarding consumer protection. This research aims to analyze legal gaps in consumer protection when e-commerce platforms face bankruptcy and examine the urgency of repositioning consumer protection mechanisms in the context of digital bankruptcy. The research employs a normative juridical approach with comparative analysis of existing bankruptcy and consumer protection regulations. The findings reveal that conventional bankruptcy provisions in Law No. 37 of 2004 are inadequate to accommodate the unique characteristics of digital platforms, particularly regarding consumer fund protection, resolution of pending transactions, and responsibility for consumer personal data. This situation is exacerbated by weak coordination between consumer protection agencies and curators in bankruptcy proceedings. The research recommends the need for lex specialis reformulation governing digital platform bankruptcy with consumer protection as the primary priority, establishment of specially protected escrow account mechanisms, and strengthening the role of BPSK (Consumer Dispute Settlement Agency) in handling digital bankruptcy disputes.